2005
DOI: 10.1111/j.1600-0668.2005.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of surrogate markers of biological agents in air and settled dust samples to evaluate a water-damaged hospital

Abstract: Detection and quantification of nonculture-based microbiological markers and/or agents of disease may be useful methods to assess microbial contamination and to more accurately evaluate microbial exposures in the indoor environment for exposure-response studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…Five of the residences that we sampled, all in the moderately to heavily water-damaged areas, had endotoxin concentrations greater than 45 EU/m 3 . Glucans are a component of fungal cell walls and have been used as an indicator of total fungal biomass (4,15). We found that glucan levels correlated significantly with airborne spore counts but not culturable fungal levels, possibly because measures of culturable fungi underestimate the airborne fungal load (10).…”
Section: Discussionmentioning
confidence: 73%
“…Five of the residences that we sampled, all in the moderately to heavily water-damaged areas, had endotoxin concentrations greater than 45 EU/m 3 . Glucans are a component of fungal cell walls and have been used as an indicator of total fungal biomass (4,15). We found that glucan levels correlated significantly with airborne spore counts but not culturable fungal levels, possibly because measures of culturable fungi underestimate the airborne fungal load (10).…”
Section: Discussionmentioning
confidence: 73%
“…On the surfaces of ventilation ducts, dust loads can range from less than 1 g/m 2 to loads in excess of 100 g/m 2 (Nielson et al 1990;Laatikainen et al 1991;Pasanen et al 1992;EPA 1996;Fortmann et al 1997;Möritz et al 2001;Kolari et al 2005;Lavoie et al 2011). On hard flooring, such as vinyl, linoleum, and hardwood, dust loading is typically in the range of 0.1-1 g/m 2 , although lighter and heavier dust loads are commonly reported (Adgate et al 1995;Rao et al 2005;Johnson et al 2009;Hoh et al 2012). The wide range of dust loads suggests that there can exist different types of particle deposits on indoor surfaces, including both monolayer and multilayer deposits (Tovey and Ferro 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches to characterizing fungal fragments have used the detection of fungal biomarkers, including (1¡3)-beta-D-glucans (10,19,21,23,25,29), N-acetyl-glucosaminase (23), fungal antigens (7), and mycotoxins (26,27), in the submicronic particle fractions (21,22,25,30,31). Some of these studies were confounded by imperfect size separation of the systems utilized since the presence of larger particles such as spores has been demonstrated in the assumed submicronic fraction (10,23,29).…”
mentioning
confidence: 99%
“…were subjected to air jets under controlled conditions (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). These particles have been suggested to be fungal fragments and important sources of allergens (16)(17)(18), antigens (7), (1¡3)-beta-D-glucans (19)(20)(21)(22)(23)(24)(25), and mycotoxins (26,27). Exposure to fungal submicronic particles may therefore provide an explanation for health effects observed in moldy indoor environments (28).…”
mentioning
confidence: 99%